Differential Mutation Detection Capability Through Capture-Based Targeted Sequencing in Plasma Samples in Hepatocellular Carcinoma - Gao, Jian; Xi, Lei; Yu, Rentao; Xu, Huailong; Wu, Min; Huang, Hong (Frontiers in Oncology, 2021)
Circulating tumor DNA (ctDNA) is a promising biomarker for accurate monitoring and noninvasive assessment of tumor burden and treatment response. Here, targeted next generation sequencing (NGS) with a designed gene panel of 176 cancer-relevant genes was used to assess mutations in 90 ctDNA samples from patients with multiple types of liver disease and 10 healthy donor samples for control. Using our ctDNA detection panel, we identified mutations in 98.89% (89/90) of patient plasma biopsy samples, and 19 coding variants located in 10 cancer-related genes (ACVR2A, PCLO, TBCK, adhesion G protein-coupled receptor (ADGRV1), COL1A1, GABBR1, MUC16, MAGEC1, FASLG, and JAK1) were identified in 96.7% of patients (87/90). The 10 top mutated genes were tumor protein p53 (TP53), ACVR2A, ADGRV1, MUC16, TBCK, PCLO, COL11A1, titin (TTN), DNAH9, and GABBR1. TTN and TP53 and TTN and DNAH9 mutations tended to occur together in hepatocellular carcinoma samples. Most importantly, we found that most of those variants were insertions (frameshift insertions) and deletions (frameshift deletions and in-frame deletions), such as insertion variants in ACVR2A, PCLO, and TBCK; such mutations were detected in almost 95% of patients. Our study demonstrated the feasibility of clinically useful targeted NGS-based ctDNA mutation profiling to guide treatment decisions in cancer.